The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2147/ijn.s202256
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of commercial and green synthesized ZnO NPs in murine model of chloroquine-induced pruritus</p>

Abstract: Purpose: To investigate the effects of zinc oxide nanoparticles (ZnO NPs) on chloroquine (CQ)-induced itching, and overall behavior of mice after oral administration of ZnO NPs of various sizes and doses. Background: With the wide-spread use of ZnO NPs in pharmaceuticals and cosmetics, concerns about their safety and toxicity are also increasing. Multiple aspects of ZnO NPs regarding cytotoxicity and tolerability are under investigation globally. Still, a clear conclusion abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…On the other hand, the high resolution in the image (Fig. 5b) clearly represents that ZnO NPs possess rod like morphology ranged from 2 µm to 0.5 µm (35). The reason for agglomeration can be due to the existence of phytochemical moieties on the surface of the particles or due to the experimental conditions in the synthesis like pH of the medium, temperature etc.…”
Section: Sem and Edaxmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, the high resolution in the image (Fig. 5b) clearly represents that ZnO NPs possess rod like morphology ranged from 2 µm to 0.5 µm (35). The reason for agglomeration can be due to the existence of phytochemical moieties on the surface of the particles or due to the experimental conditions in the synthesis like pH of the medium, temperature etc.…”
Section: Sem and Edaxmentioning
confidence: 98%
“…7). .The free ZnO NPs showed that the plant extract can lower ZnO ions and prevent them from aggregating as a result of the bio molecules acting as protective agents (35).…”
Section: Tem Analysismentioning
confidence: 99%
“…Nanomaterials are widely used in the development of topical drug delivery systems due to their superior drug-carrying properties. To increase percutaneous drug penetration, prolong the release time and reduce side effects, some analgesics, such as nonsteroidal anti-inflammatory drugs, local anesthetics, capsaicin, and antipruritic drugs, such as glucocorticoids, have been developed as nanoemulsions, transfersomes, solid lipid nanoparticles (SLNs) and as other systems for the treatment of pain and itching after healing.In addition, topical ZnO NPs have been observed to have anti-itch effects (Aman et al, 2019;Andreu et al, 2018;Bikkad et al, 2014;Ghiasi et al, 2019;Nafisi et al, 2018).These formulations are feasible for most kinds of wounds, such as postoperative wounds, diabetic wounds, and burn wounds. However, postherpetic neuralgia woundsare a special circumstance.…”
Section: 3skin Sensory Regulationmentioning
confidence: 99%